DNA Methylation Silences Exogenous Gene Expression in Transgenic Birch Progeny - Ma, Minghao; Chen, Xiaohui; Yin, Yibo; Fan, Ruixin; Li, Bo; Zhan, Yaguang; Zeng, Fansuo (Frontiers in Plant Science, 2020)
The genetic stability of the foreign gene in progeny of transgenic trees is very important in forest breeding. Transgenic Betula platyphylla and F1 were selected as the experiment materials in order to determine genetic expression stability of foreign genes and explore the mechanism of gene silence.Studies on F1 transgenic plants of different hybrid combination showed that foreign gene was separated in the process of genetic transmission. The expression level of bgt gene in hybrid progeny WT1×TP22 (184) and WT1×TP23 (212) was higher than that of the parental, TP22 and TP23. While the relative expression of the gene silencing plant TP23×TP49 (196 ) was only 13. 5% of its parental expression.The methylation rate of the promoter region and coding region of the bgt gene in gene silencing plant was at 32. 35%~45. 95%, while the methylation rate in exogenous gene normally expressed hybrid progeny was relative low, at 0~29. 73%. This indicates that gene silencing is caused by high rate of cytosine methylation. The relative expression level of the methyltransferases BpCMT, BpDRM and BpMET in the foreign gene silenced plant 196 (TP23 × TP49) were 2. 54 times, 9. 92 times, and 4. times higher than that of their parents, respectively. This is consistent with the high methylation level of the exogenous gene in 196, and also shows that the methyltransferases, BpCMT, BpDRM and BpMET are closely related to the silencing of the exogenous gene.